RESECTION URETHRA ANASTOMOSIS END TO END IN THE CURRENT CONDITIONS OF DEVELOPMENT UROLOGY - V. V. Krasulin (Вестник урологии)
The article presents a review of the place in practical urology and opportunities resection urethral stricture and obliteration with various localization and extent. This opinion is based on the experience of the author, dealing with this issue for over 50 years. The author highlights the historical aspects of the development and implementation of this surgery method in clinical practice, as well as contribute to the solution of this problem, the doctors of the Rostov school of urology during the last ten years.